Totally chlorine free (TCF) multistage peroxide bleaching of kenaf bast pulp at different duration - Jagedeswary Erison (2024)
There is an increasing of global demand of paper and needed short rotation pulpwood. Hibiscus cannabinus also known as Kenaf is a species of fast-growing warm-season annual. There are still limited of scholarly information of Kenaf as pulpwood. Kenaf fibre is much suitable to bleached using mild bleaching agent such as hydrogen peroxide. This research aims to provide information of multistage peroxide bleaching effect on the mechanical properties and optical properties of handsheet made from the pulp that derived from kenaf. This including tensile strength and bursting strength. The process of pulping is for remove the lignin without loosing the fibre’s strength. Bleaching stages are designed to completely remove the remaining lignin because only 80% to 90% maximum can removed during the pulping. Pulp produced from using Kenaf was bleached with hydrogen peroxide at the 3%wt based on the weight of pulp, respectively. According to standard of TAPPI, the mechanical properties and brightness of handsheet made from bleached pulp were evaluated. Handsheet made from bleached pulp have had their brightness improved by increasing the bleaching time. Moreover, bleaching duration of 60 minutes produces pulp with maximum brightness. On the other hand, mechanical properties of handsheet were increase from 0 minutes to 60 minutes. Multistage peroxide bleaching to a certain extent are capable of improving both the optical properties and mechanical properties of handsheets made from Kenaf pulp. Excessive bleaching times can also have a negative impact on the mechanical properties of kenaf bast handsheets. Based on the overall results, this study can conclude that kenaf bast pulp has the potential to improve the properties of handsheet.